If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3n + 5)(n + -2) + -3n(n + 1) = 6 Reorder the terms: (5 + 3n)(n + -2) + -3n(n + 1) = 6 Reorder the terms: (5 + 3n)(-2 + n) + -3n(n + 1) = 6 Multiply (5 + 3n) * (-2 + n) (5(-2 + n) + 3n * (-2 + n)) + -3n(n + 1) = 6 ((-2 * 5 + n * 5) + 3n * (-2 + n)) + -3n(n + 1) = 6 ((-10 + 5n) + 3n * (-2 + n)) + -3n(n + 1) = 6 (-10 + 5n + (-2 * 3n + n * 3n)) + -3n(n + 1) = 6 (-10 + 5n + (-6n + 3n2)) + -3n(n + 1) = 6 Combine like terms: 5n + -6n = -1n (-10 + -1n + 3n2) + -3n(n + 1) = 6 Reorder the terms: -10 + -1n + 3n2 + -3n(1 + n) = 6 -10 + -1n + 3n2 + (1 * -3n + n * -3n) = 6 -10 + -1n + 3n2 + (-3n + -3n2) = 6 Reorder the terms: -10 + -1n + -3n + 3n2 + -3n2 = 6 Combine like terms: -1n + -3n = -4n -10 + -4n + 3n2 + -3n2 = 6 Combine like terms: 3n2 + -3n2 = 0 -10 + -4n + 0 = 6 -10 + -4n = 6 Solving -10 + -4n = 6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -4n = 6 + 10 Combine like terms: -10 + 10 = 0 0 + -4n = 6 + 10 -4n = 6 + 10 Combine like terms: 6 + 10 = 16 -4n = 16 Divide each side by '-4'. n = -4 Simplifying n = -4
| G-72=36 | | -14-63-(-52)= | | 4x-2-4= | | -6-6p+-1= | | -2(-7x+3)+3x=8x-15 | | 27th=-3w | | log^3(3x+8)=log^3(x^2+x) | | 3x-24+x=180 | | 2n^2+2n=4 | | 0.05x+0.09(10000-1x)=240 | | 4y=-1x+5 | | 87-(-34)+13= | | 3/5*5/6= | | 3(x-8)=2(3x+21) | | 67+20x=-3+15x | | 4x+8=2x+54 | | X-12=y+7 | | 2(-3/4x-3/4) | | 9b(2b+5)+4b(6b+6)= | | 8+12n-6=9n+56-6n | | 4x+30+9x+42=104 | | 180=2(2x+2)+3x+1 | | -3x-8(16)=-2 | | (5/4)4/5x=36(5/4) | | 9x-(4x-22)=67 | | 60=40+2w | | (32X^-10*Y^4/7)^3/5 | | 9x+9x=4 | | 3-4(x+6)=3 | | (8m+5)(8m-5)=0 | | 7+10s+-1s+1s= | | -82-5x=3x+54 |